Elite female basketball players' body-weight neuromuscular training and performance on the Y-balance test - Benis, R.; Bonato, M.; La Torre, A. (Journal of Athletic Training, 2016)
Context: Neuromuscular training enhances unconscious motor responses by stimulating both the afferent signals and central mechanisms responsible for dynamic joint control. Dynamic joint-control training is a vital component of injury-prevention programs.